Race, Religion, and Global Solidarities: W. E. B. Du Bois and "The Black Church" as a Contested Category - Baumann, Roger (Journal for the scientific study of religion, 2023)
W.E.B. Du Bois was thoroughly ambivalent about the political significance of American Black churches regarding their role in challenging racial inequality. He saw them as integral to Black social life, but also as failing to live up to their potential as drivers of liberation. And, while he focused primarily on Black churches within the United States, Du Bois was also committed to Black liberation on a global level. This suggests great potential for applying DuBois’ analyses of Black religion to the question of transnational religious and racial solidarities and the global political salience of "the Black Church" as a category. In this context, this article explores the significance of DuBois’ work for analyzing the category of "the Black Church." It does so through a comparative case study of African American Christian engagement with the issue of Israel and Palestine, with four case studies ranging from African American Christian Zionists to Palestinian solidarity activists. Across these cases, the analysis highlights the ways that the history, identity, and mission of "the Black Church" are invoked in the context of Palestine and Israel. It argues that "the Black Church" is best understood as a contested category of collective religious and racial identity.